บทบาทของพระสงฆ์ที่มีต่อประชาชนในการพัฒนาท้องถิ่น ตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ - ., พระครูอนุกูลปริยัติการ; ศิลารัตน์, พัชรี; ., พระครูโพธิธรรมานุศาสก์; ภูเยี่ยมจิตร, ณรงค์ (วารสารพุทธปรัชญาวิวัฒน์, 2025)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาบทบาทของพระสงฆ์ที่มีต่อประชาชนในการพัฒนาท้องถิ่นตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ 2) เพื่อศึกษาปัญหา หรืออุปสรรค ของพระสงฆ์ที่มีต่อประชาชนในการพัฒนาท้องถิ่นตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ 3) เพื่อศึกษาข้อเสนอแนะแนวทางการแก้ไขปัญหาบทบาทพระสงฆ์ที่มีต่อประชาชนในการพัฒนาท้องถิ่นตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ กลุ่มตัวอย่าง ได้แก่ ประชาชนที่เป็นตัวแทนครัวเรือนที่อยู่ในเขตการปกครองตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ จำนวน 361 คน เครื่องมือที่ใช้เป็นแบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน สถิติที่ใช้ในการทดสอบสมมติฐานโดยใช้ t-test ผลการวิจัยพบว่า 1) บทบาทของพระสงฆ์ที่มีต่อประชาชนในการพัฒนาท้องถิ่นตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ โดยภาพรวมอยู่ในระดับมาก โดยเรียงลำดับความสำคัญค่าเฉลี่ยจากมากไปหาน้อยได้ ดังนี้  ด้านวัฒนธรรม รองลงมาด้านการศึกษา และด้านสังคม 2) ปัญหาหรืออุปสรรคของพระสงฆ์ที่มีต่อประชาชนในการพัฒนาท้องถิ่นตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ในด้านสังคม การประพฤติตัวของพระสงฆ์บางรูปยังไม่เหมาะสมจึงทำให้ประชาชนไม่เคารพศรัทธา ด้านการศึกษา ขาดพระสงฆ์ที่มีความชำนาญในการถ่ายทอดความรู้ และด้านวัฒนธรรม การเผยแผ่ยังไม่ดึงดูดความสนใจของวัยรุ่น หรือคนรุ่นใหม่  3) ข้อเสนอแนะแนวทางการแก้ไขปัญหาบทบาทพระสงฆ์ที่มีต่อประชาชนในการพัฒนาท้องถิ่นตำบลยางตลาด อำเภอยางตลาด จังหวัดกาฬสินธุ์ ด้านสังคม คือพระสงฆ์ต้องเข้ามามีส่วนร่วมคิด ร่วมทำ ร่วมแก้ปัญหากับชุมชนอย่างแท้จริงและควรสนับสนุนส่งเสริมกิจกรรมในด้านสังคมต่อชุมชน อย่างจริงจังและต่อเนื่อง ด้านการศึกษา คือ ภาครัฐควรจัดหาเอกสาร สื่อ อุปกรณ์ที่ทันสมัย ให้แก่พระสงฆ์ได้ใช้ในการเรียนการสอนแก่เยาวชน และด้านวัฒนธรรม คือชุมชนควรให้ความร่วมมือกับพระสงฆ์มากกว่าที่เป็นอยู่ในปัจจุบันนี้ และควรให้พระสงฆ์มีส่วนรวมในการจัดการแนวทางอนุรักษ์ร่วมกับโรงเรียนในชุมชน The objectives of the research were 1) To study the role of monks towards the people in the local development of Yang Talat Subdistrict, Yang Talat District, Kalasin Province. 2) To study the Problems or obstacles monks have with the people in local development in Yang Talat Subdistrict, Yang Talat District, Kalasin Province. 3) To study Suggestions for ways to solve the problem of the role of monks in the people in local development, Yang Talat District, Kalasin Province. Sample group Used in this research were people representing households in the administrative area of Yang Talat Subdistrict, Yang Talat District, Kalasin Province, totaling 361 people. The tool used is a questionnaire. Statistics used in data analysis include frequency, percentage, mean, and standard deviation. Statistics used to test hypothesis using t-test. The results of the research found that 1) The role of monks towards the people in the local development of Yang Talat Subdistrict, Yang Talat District, Kalasin Province. Overall, it is at a high level. The average values can be arranged in order of importance from highest to lowest as follows: cultural aspect, followed by education and social aspect. 2) Problems or obstacles of the monks towards the people in local development in Yang Talat Subdistrict, Yang Talat District, Kalasin Province. In terms of society, the behavior of some monks is still inappropriate, causing people to not respect their faith. In terms of education, there is a lack of monks who have the expertise to transmit knowledge. And cultural Apocalypse has not yet caught the attention off teenagers. Or the new generation. 3) Suggestions on how to solve the problem of the role of monks in the people in local development in Yang Talat Subdistrict, Yang Talat District, Kalasin Province. The social aspect is that the monks must truly participate in thinking, doing, and solving problems with the community and should support and promote social activities to the community. Seriously and continuously. In terms of education, the government sector should provide modern documents, media, and equipment. Given to monks to use in teaching youth. And cultural That is, the community should cooperate with the monks more than and cultural That is, the community should cooperate with the monks more than is currently the case. And monks should be involved in managing conservation guidelines together with schools in the community.